Empowering Entrepreneurs: Financial Literacy, Culltural Exchange, and Human Resource Develompment at PERMAI Pulau Pinang, Malaysia - Haanurat, A Ifayani; Jam’an, Andi; Muchran, Muchriana; Syukur, Alam Tauhid; Arsyad, Arsyad; Rahman, Wahyudin; Pratiwi, Nurul Rezky (IJCS: International Journal of Community Service, 2024)
This community service initiative aims to develop young people's entrepreneurial capabilities and access to economic opportunities for the migrant worker community in Pulau Pinang, Malaysia. The PERMAI organization conducts training sessions for the participants who become equipped with the necessary knowledge on topics like financial literacy, basic business management, and human resource development. Along with the theoretical part of the program, practical workshops and cultural exchange activities are incorporated, which promote knowledge sharing as well as closer interpersonal connections. This method of teaching not only offers professional qualifications but also helps in breaking the cultural barriers and thus, a feeling of togetherness and a common goal among the participants is developed. The program is a recognition of diverse challenges that migrant youth go through, such as economic and social vulnerabilities, hence, it is designed in such a way to resolve these problems. The results are encouraging — the participants show increased capability in making financial decisions as well as to develop a feasible business plan. The findings underscore the feasibility of the program as an international scalable model for empowering marginalized communities, based on the intersection of skill-building and cultural understanding to facilitate real change.